Protein Farnesyltransferase Catalyzes Unanticipated Farnesylation and Geranylgeranylation of Shortened Target Sequences - Ashok, Sudhat (Biochemistry, 2020)
Protein prenylation is a posttranslational modification involving the attachment of a C15 or C20 isoprenoid group to a cysteine residue near the C-terminus of the target substrate by protein farnesyltransferase (FTase) or protein geranylgeranyltransferase type I (GGTase-I), respectively. Both of these protein prenyltransferases recognize a C-terminal “CaaX” sequence in their protein substrates, but recent studies in yeast- and mammalian-based systems have demonstrated FTase can also accept sequences that diverge in length from the canonical four-amino acid motif, such as the recently reported five-amino acid C(x)(3)X motif. In this work, we further expand the substrate scope of FTase by demonstrating sequence-dependent farnesylation of shorter three-amino acid “Cxx” C-terminal sequences using both genetic and biochemical assays. Strikingly, biochemical assays utilizing purified mammalian FTase and Cxx substrates reveal prenyl donor promiscuity leading to both farnesylation and geranylgeranylation of these sequences. These findings expand the substrate pool of sequences that can be potentially prenylated, further refine our understanding of substrate recognition by FTase and GGTase-I, and suggest the possibility of a new class of prenylated proteins within proteomes.